Brill's companion to the reception of Aristotle in antiquity - Falcon, Andrea. (Brill's Companions to Classical Reception, 2016)
Brill's Companion to the Reception of Aristotle provides a systematic yet accessible account of the reception of Aristotle's philosophy in Antiquity. To date, there has been no comprehensive attempt to explain this complex phenomenon. This volume fills this lacuna by offering broad coverage of the subject from Hellenistic times to the sixth century AD. It is laid out chronologically and the 23 articles are divided into three sections: I. The Hellenistic Reception of Aristotle; II. The Post-Hellenistic Engagement with Aristotle; III. Aristotle in Late Antiquity. Topics include Aristotle and the Stoa, Andronicus of Rhodes and the construction of the Aristotelian corpus, the return to Aristotle in the first century BC, and the role of Alexander of Aphrodisias and Porphyry in the transmission of Aristotle's philosophy to Late Antiquity.